2020
DOI: 10.1017/jmech.2019.63
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Characteristics in Micromachining of Single Crystal 6H-SiC: Insight into Slip Systems Activation

Abstract: Silicon carbide (SiC) is ideally suitable as a sensor material in harsh environments. Despite the brittleness in the macroscopic scale, plasticity in SiC is observed at small component length-scales. Previous nanoindentation based study combining experiment and numerical approaches of single-crystal 6H-SiC has shown that slip activation is rather complex, and that non-basal slip could potentially dominate the plastic deformation behaviour. In this study, we investigated the local deformation response evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The modulus and hardness increase with increasing indentation depth in the initial stage, but finally reach a stable value equivalent to that of single crystal 6 h SiC. Pang et al [19] explored the evolution of the local deformation response of direct and nearby shear strains at the indenter tip and found that the cone slip family contributes greatly to the deformation process. Leide et al [20] studied indentation deformation using high-resolution electron backscatter diffraction and Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The modulus and hardness increase with increasing indentation depth in the initial stage, but finally reach a stable value equivalent to that of single crystal 6 h SiC. Pang et al [19] explored the evolution of the local deformation response of direct and nearby shear strains at the indenter tip and found that the cone slip family contributes greatly to the deformation process. Leide et al [20] studied indentation deformation using high-resolution electron backscatter diffraction and Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%